The Meaning of Batik Motifs in Tando Pusako Batik House in Mukomuko Regency - Efrashia, Tiara Husnun; Efi, Agusti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The Tando Pusako Batik House in Mukomuko Regency, Bengkulu Province, faces the challenge of public understanding of the motifs and meanings of batik that are still not conveyed. This research aims to describe the meaning of Tando Pusako batik motifs through qualitative methods by collecting data from observations, interviews, and documentation. Data analysis follows the Miles and Huberman model, including collection, reduction, data presentation, and conclusion drawn. The results of this study prove that there are several meanings of batik motifs, including: 1) The Cerano motif in Tando Pusako batik means respect. 2) The mikih fish motif in Tando Pusako batik has a meaning, which reflects gratitude. 3) The Lokan motif in Tando Pusako batik has the meaning of advice to humans that in social life we help each other. 4) The oil palm tree motif in Tando Pusako batik has the meaning of prosperity and abundance of property. 5) The Rafflesia flower motif in Tando Pusako batik has the meaning of earth fertility. 6) The Mangrove Plant motif in Tando Pusako batik has the meaning of perseverance in facing challenges and changes in life. 7) The Basurek motif (Arabic Calligraphy) in Tando Pusako batik has a religious meaning. For further research, research can be carried out on how to transform the source of the idea of Tando Pusako batik motifs which has meaning for Mukomuko district.